The Influence of Students' Perceptions of Teachers' Teaching Methods, Learning Styles, Locus of Control, Family Environment, and Peer Environment on the Learning Achievement of Class XI Students in Economics - Nisa Ilhafiza; Yosi Eka Putri; Stevani (Global Action and Education for Society, 2025)
This study aims to determine: 1) the effect of students' perceptions of teachers' teaching methods on students' academic achievement, 2) the effect of learning styles on students' academic achievement, 3) the effect of locus of control on students' academic achievement, 4) the effect of family environment on students' academic achievement, 5) the effect of peer environment on students' academic achievement, and 6) the combined effect of students' perceptions of teachers' teaching methods, learning styles, locus of control, family environment, and peer environment on students' academic achievement. This research was conducted in August 2025. The type of research is descriptive and associative. The population studied consists of all 77 Grade XI students at SMA Negeri 1 Hiliran Gumanti, selected using total sampling technique. Data were collected through a questionnaire that has been tested for validity and reliability, as well as documentation of students' grades. Data analysis was performed using Multiple Linear Regression, employing t-tests and F-tests. The results of the study, assisted by SPSS and Eviews software, indicate that: (1) students' perceptions of teachers' teaching methods have a positive and significant effect on academic achievement with a coefficient value of 0.355, where the t-value is 2.149 > t-table 1.665, (2) students' learning styles have a positive and significant effect on academic achievement with a coefficient value of 0.255, where the t-value is 2.576 > t-table 1.665, (3) locus of control has a positive and significant effect on academic achievement with a coefficient value of 0.311, where the t-value is 2.298 > t-table 1.665, (4) family environment has a positive but not significant effect on academic achievement with a coefficient value of 0.204, where the t-value is 1.276 < t-table 1.665, (5) peer environment shows a positive and significant effect on academic achievement with a coefficient value of 0.357, where the t-value is 2.308 > t-table 1.665, and (6) collectively, the influence of students' perceptions of teachers' teaching methods, learning styles, locus of control, family environment, and peer environment has a significant effect on students' academic achievement, where the F-value is 16.555 > F-table 2.34.